Activation of protease-constitutive recA proteins of Escherichia coli by rRNA and tRNA. - Wang, W B (1988)
The RecA proteins of the unusually strong protease-constitutive mutants recA1202 and recA1211 can use RNA in addition to single-stranded DNA (ssDNA) as a cofactor in the cleavage of the LexA repressor in vitro. In the presence of rRNA or tRNA, the effectiveness of these proteins decreased in the order RecA1202 greater than RecA1211 much greater than RecA+, which is also the order of their in vivo constitutive protease activities. The effectiveness of rRNA was comparable to that of ssDNA in the cleavage of the LexA repressor by either mutant protease. Although all the common nucleoside triphosphates can act as positive effectors for LexA cleavage by the two mutant proteins in the presence of ssDNA (W. B. Wang, M. Sassanfar, I. Tessman, J. W. Roberts, and E. S. Tessman, J. Bacteriol. 170:4816-4822, 1988), only dATP, ATP, and ATP-gamma-S were effective in the presence of RNA. Our results explain more fully why certain recA mutants have high constitutive protease activities in vivo.